The problem of staffing management of environmental management and environmental activities (Pedagogy of Higher and Secondary Education, 2012)
Shofolov D. L. The problem of staffing management of environmental management and environmental activities.The article deals with the need for environmental and legal training on environmental management and environmental management, offers the master's programs for professionals in specialty 8.18010005 – «Environmental Policy and Law» at the National University of Life and Environmental Sciences of Ukraine.
Keywords: эколого-правовая подготовка; управления природопользованием и природоохранной деятельностью